Hydroxychloroquine in a G6PD-Deficient Patient with COVID-19 Complicated by Haemolytic Anaemia: Culprit or Innocent Bystander - François Mastroianni; Vincent Colombie; Géraldine Claes; Axelle Gilles; Frédéric Vandergheynst; Sammy Place (European Journal of Case Reports in Internal Medicine, 2020)
Hydroxychloroquine has been used worldwide as a first-line treatment for patients hospitalized with COVID-19. Little is known about COVID-19 and its effects on patients with congenital red blood cell disorders. We report a case of haemolytic anaemia in a 32-year-old patient and a fortuitous highlighting of G6PD deficiency. We reviewed the literature to assess the risk of hydroxychloroquine use in this context.